Slip-sliding away - Some Reflections on Recent Developments in Copyright and their Consequences - Nilsson, Kjell (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
Copyright is undoubtedly a very complicated matter. For that very reason it might be useful now and again to look beyond the jungle of treaties, directives, laws, decrees and contracts, and try to establish where we are actually heading. Then we can ask ourselves whether the direction taken is the one we would like to see. My purpose in writing this article is to demonstrate how the ‘balance’, which was always considered to be a crucial goal of copyright regulation, has been gradually undermined, to the detriment of the consumers of information and culture. I will also try to illustrate how copyright has become distanced from what was once its very foundations. If we look more closely at recent developments there are primarily two factors which merit special attention, namely 1) the widespread revision of copyright legislation and 2) The increasing regulation by contract.